Verrucous sarcoidosis of the skin simulating squamous cell carcinoma - Pezzetta, S.; Zarian, H.; Agostini, C.; Salmaso, R.; Alaibac, M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Here, we report a case of a 38-year-old woman with a history of systemic sarcoidosis who developed cutaneous verrucous sarcoidosis simulating a squamous cell carcinoma. This modality of presentation is unusual in both caucasic patients and in woman and may represent a diagnostic challenge for dermatologists.